2018
DOI: 10.1007/s00345-018-2320-9
|View full text |Cite
|
Sign up to set email alerts
|

Ureteroscopy is more cost effective than shock wave lithotripsy for stone treatment: systematic review and meta-analysis

Abstract: IntroductionA rising incidence of kidney stone disease has led to an increase in ureteroscopy (URS) and shock wave lithotripsy (SWL). Our aim was to compare the cost of URS and SWL for treatment of stones.MethodsA systematic review and meta-analysis based on Cochrane and PRISMA standards was conducted for all studies reporting on comparative cost of treatment between URS and SWL. The cost calculation was based on factual data presented in the individual studies as reported by the authors. English language arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 28 publications
1
54
0
5
Order By: Relevance
“…Similarly, among four patients from URS group, 75% were successfully treated with second session of URS and 25% case required PCNL because of stone migration. The re-treatment or auxillary treatment rates between ESWL and URS were 20% and 25% with ESWL and URS group which are similar to the study by Geraghty RM et al 13 Both ESWL and URS treatment have been shown to be safe and effective but requires expensive equipments and urological expertise. The complication rate was higher with URS in comparison to ESWL because URS is more invasive, requiring anaesthesia.…”
Section: Discussionsupporting
confidence: 85%
“…Similarly, among four patients from URS group, 75% were successfully treated with second session of URS and 25% case required PCNL because of stone migration. The re-treatment or auxillary treatment rates between ESWL and URS were 20% and 25% with ESWL and URS group which are similar to the study by Geraghty RM et al 13 Both ESWL and URS treatment have been shown to be safe and effective but requires expensive equipments and urological expertise. The complication rate was higher with URS in comparison to ESWL because URS is more invasive, requiring anaesthesia.…”
Section: Discussionsupporting
confidence: 85%
“…Also, not all were in a ureteric stone population. A recent systematic review on costing studies of URS vs ESWL confirmed a lack of cost‐utility analyses, particularly from a UK relevant perspective, and found studies were conflicting on whether ESWL or URS is more costly, but these are mostly USA or Chinese studies where intervention costs cannot be compared to the UK. There are differing financial incentives even in countries with similar healthcare systems to the UK, e.g., in Germany ESWL always requires an admission, and the length of stay can also vary according to the healthcare system.…”
Section: Discussionmentioning
confidence: 99%
“…Rob et al reported that there was no significant difference in the complication rates of URS (both major and minor) between medium and highvolume paediatric centres [24]. A recent meta-analysis by Geraghty et al also found the overall cost of URS procedure to be lower than SWL ($2801) compared to SWL ($3627) ($2801 vs. $3627, p = 0.03) [25].…”
Section: Role Of Swl and Pcnlmentioning
confidence: 99%